ChemInform Abstract: Dehydration of Magnesium Bromide Hexahydrate Studied by in situ X‐Ray Powder Diffraction. Issue 13 (18th March 2013) - Dinnebier, Robert E.; Runcevski, Tomce; Sugimoto, Kunihisa
Abstract The dehydration process of MgBr2·6H2O is characterized by powder XRD in the temperature range of 300—420 K.